2019
DOI: 10.1039/c9nr01072f
|View full text |Cite
|
Sign up to set email alerts
|

Doping of epitaxial graphene by direct incorporation of nickel adatoms

Abstract: Ni adatoms incorporated in epitaxial graphene during growth on Ni(111) are identified by scanning tunneling microscopy and density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The Gr surface appears sprinkled by a huge number of defects with diverse appearance. The large white spots, clearly visible in Figure 2b and in its inset (white circle), are also observed in the pristine case (see Figure S3) and have been previously assigned to Ni atoms trapped in the Gr network during the growth process [45,46]. Indeed, it has been experimentally and theoretically demonstrated that Ni surface adatoms actively participate in the CVD Gr growth, catalyzing the C-C bond formation [45], remaining at times trapped into the Gr network [27].…”
Section: Resultssupporting
confidence: 62%
“…The Gr surface appears sprinkled by a huge number of defects with diverse appearance. The large white spots, clearly visible in Figure 2b and in its inset (white circle), are also observed in the pristine case (see Figure S3) and have been previously assigned to Ni atoms trapped in the Gr network during the growth process [45,46]. Indeed, it has been experimentally and theoretically demonstrated that Ni surface adatoms actively participate in the CVD Gr growth, catalyzing the C-C bond formation [45], remaining at times trapped into the Gr network [27].…”
Section: Resultssupporting
confidence: 62%
“…Other elements like aluminum [129,130], phosphorus [131], sulfur [22], or transition metals [132][133][134][135] have also been envisioned or already tested for important applications such as hydrogen storage or oxygen reduction reactions. To our knowledge however, only Mo- [136] and recently Ni-doped [137] graphene have been characterized with STM, calling for further investigation of the electronic properties of graphene doped with these elements.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…TM adatoms also show higher stability on phosphorene compared with non-transition metal atoms such as C, N, O, Li, Na, and Mg, which are bonded to phosphorene with a binding energy of 0.6-5.3 eV [12,14,15,18]. On the other hand, the substitutional doping of phosphorene with stable binding energies, and comparable to those on substitutionally doped graphene with metal and semimetallic atoms, where binding energies of 0.6-9.6 eV are reported [11,[42][43][44][45][46]. In this way, a wide series of atoms (including metals, alkaline metals, transition metals, metalloids, non-metals, and halogens) can be substitutionally introduced into phosphorene with binding energies of 2.1-9.2 eV [18,22,38].…”
Section: Introductionmentioning
confidence: 89%